Diasporic consciousness and Bollywood : South African Indian youth and the meanings they make of Indian film - Boshoff, Priscilla A (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2006)
A particular youth identity in the South African Indian diaspora is being forged in a nexus o flocal and global forces . The globalisation of Bollywood and its popularity as a global media and the international commodification of the Indian exotic have occurred at the same time as the valorisation of 'difference' in the local political landscape. Indian youth, as young members of the South African Indian diaspora, are inheritors both of a conservative - yet adaptable - home culture and the marginalised identities of apartheid. However, the tensions between their desire to be recognised as both 'modern' South Africans and as ' traditional ' Indians create a space in which they are able to (re)create for themselves an identity that can encompass both their home cultures and the desires of a Westernised modernity through the tropes of Bollywood. Bollywood speaks to its diasporic audiences through representations of an idealised 'traditional yet modern' India. Although India is not a place of return for this young generation, Bollywood representations of successful diasporic Indian culture and participation in the globalised Bollywood industry through concerts and international award ceremonies has provided an opportunity for young Indians in South Africa to re-examine their local Indian identities and feel invited to re-identify with the global diasporas of India.
Keywords: Motion pictures -- India; Youth -- South Africa -- Attitudes; East Indians -- South Africa -- Attitudes; Motion picture industry -- India -- Mumbai